Method for obtaining at least one ceramic component by joining at least two ceramic SIC preforms and ceramic component obtained by said method

By applying a bonding slurry with a specific composition to the surface of a SiC preform and performing Si infiltration, the problem of insufficient stability in the joint seam of the SiC preform is solved, enabling the manufacture of high-strength SiSiC components suitable for ceramic substrates in the electronics, automotive, and pharmaceutical industries.

CN120882676APending Publication Date: 2025-10-31CERAMTEC GMBH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202480018273.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-15
Filing Date
2024-02-28
Publication Date
2025-10-31

AI Technical Summary

Technical Problem

Existing technologies are insufficient for effectively joining SiC preforms to form large SiSiC modules, and conventional methods such as polymer adhesives or metal welding suffer from insufficient temperature and mechanical stability of the joints.

Method used

A bonding slurry containing a specific ratio of silicon carbide particles, carbon black, and binder is applied to the bonding surface of a SiC preform and dried before Si infiltration is performed to form a substantially bonded SiSiC module.

Benefits of technology

It achieves higher mechanical and temperature stability, reduces milling time and material consumption, allows for the assembly of complex 3D printed structures, improves print volume utilization, and enhances the overall strength of SiSiC components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005590695610000011
    Figure HDA0005590695610000011
  • Figure HDA0005590695610000012
    Figure HDA0005590695610000012
  • Figure HDA0005590695610000021
    Figure HDA0005590695610000021
Patent Text Reader

Abstract

The invention relates to a method for obtaining at least one ceramic component by joining at least two SiC preforms:-providing at least two porous SiC preforms, such as a green part or a coked part, each having at least one joining surface; providing a bonding slurry comprising-40 to 80 wt.%, preferably 50 to 70 wt.%, of at least one binder,-2 to 20 wt.%, preferably 5 to 18 wt.%, more preferably 8 to 15 wt.%, of silicon carbide particles having a particle size D50 of 10 to 20 [mu] m, preferably 11 to 18 [mu] m, more preferably 11 to 16 [mu] m; -8 to 25 wt%, preferably 9 to 20 wt%, more preferably 10 to 15 wt% of silicon carbide particles having a particle size D50 of 1 to 10 [mu] m, preferably D50 of 2 to 8 [mu] m, more preferably D50 of 2 to 5 [mu] m,-10 to 30 wt%, preferably 12 to 20 wt%, more preferably 13 to 18 wt% of carbon black, -wherein the sum of all the ingredients always totals 100% by weight; -pressing the joining surfaces of the at least two SiC preforms together; -drying the at least two SiC preforms; and-heating the at least two SiC preforms, whereby Si permeates into the SiC preform comprising the dried bonding slurry, thereby obtaining a substantially bonded silicon-silicon carbide (SiSiC) ceramic component.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to a method for obtaining at least one SiSiC ceramic component by joining at least two SiC preforms during infiltration with liquid silicon (Si).

[0002] describe

[0003] Ceramic substrates or components are used in various technical fields, such as the electronics, automotive, and pharmaceutical industries. Silicon carbide (SiC) is used as a ceramic substrate due to requirements for hardness, chemical resistance, and heat resistance. To produce such ceramic components, for example, a molded body made from a carbon-containing starting material can undergo a silicide process in which carbon reacts with externally supplied silicon to form silicon carbide, and, where appropriate, fill the network of pores present or formed in the molded body with pure silicon. In the latter case, where silicon permeates the pores of the molded body, a silicon-permeable silicon carbide (SiSiC) molded body is obtained, characterized by the fact that it has almost no residual porosity.

[0004] Larger ceramic substrates or components can be obtained by joining two or more smaller composites or preforms via bonding. This can include gluing with polymeric adhesives such as epoxy adhesives, or welding with metal or inorganic solders, i.e., glass. A disadvantage of this non-material bonding is the insufficient temperature, mechanical, or chemical stability of the joint.

[0005] EP 3 599 229 B1 discloses a reactive-bonded ceramic assembly comprising two structural elements and having a bonding seam made of a material having substantially the same or very similar properties to the material of the ceramic assembly or preform to be bonded. The bonding seam material comprises 30 vol% silicon carbide and at least 8 vol% silicon. At least one of the ceramic assemblies to be bonded includes at least one cavity at least partially filled with silicon and / or a silicon alloy. The cavity is adjacent to the material of the bonding seam, or the silicon in the cavity is at least partially adjacent to the material of the bonding seam. Thus, the cavity disposed in the ceramic assembly is filled with silicon and can be considered a type of silicon storage space subsequently used for material-to-material bonding of the ceramic assembly and the bonding seam.

[0006] DE 10 2011 007 815 B4 describes a method for obtaining a ceramic composite in which two preforms are formed from a carbon composite material having an amorphous porous carbon matrix, and the two preforms are bonded to each other through a bonding surface by providing a bonding paste comprising silicon carbide and a polymer binder and hardening it, and subsequently silicifying the preforms into a composite.

[0007] Ceramic composites can also be obtained through 3D printing, as described, for example, in WO 2019 / 063833 A1 or WO 2018 / 206250 A1. However, a drawback of 3D printing is that the print volume is limited by the printer design. This means that, for example, particularly large parts cannot be achieved using 3D printing. Furthermore, SiSiC from 3D printing has a coarser SiC grain size and a higher Si content. Both factors reduce mechanical properties and affect electrical properties.

[0008] The object of this invention is to provide a joining method for connecting unpermeated SiC preforms to form a SiSiC assembly after Si permeation, and more specifically, a joining method in which porous unpermeated parts made of SiC (so-called SiC preforms) can be joined during Si permeation to form a larger SiSiC assembly. The SiC preforms can be obtained by several manufacturing methods (e.g., pressing, slurry casting, tape casting, 3D printing, and / or extrusion) to form a green body, which can be further shaped by processing. The green parts can be heated between 800°C and 1250°C to obtain coked parts, thereby providing better mechanical stability for processing and / or permeation steps. In this case, a joining slurry is needed that remains in the joining area and is not drawn into the assembly in the case of highly coarse-pore components.

[0009] Therefore, a method is provided for obtaining at least one SiSiC ceramic component by connecting at least two SiC preforms, the method comprising the following steps:

[0010] - Provide at least two porous SiC preforms, each having at least one connecting surface, such as green parts or coking parts;

[0011] - Provides a bonding slurry containing

[0012] -40% to 80% by weight, preferably 50% to 70% by weight, of at least one adhesive.

[0013] -2% to 20% by weight, preferably 5% to 18% by weight, more preferably 8% to 15% by weight of particle size D 50 (DIN EN 725-5, ISO 13320) 10μm to 20μm, preferably D 50 The thickness is 11 μm to 18 μm, more preferably D. 50 Silicon carbide particles ranging from 11 μm to 16 μm

[0014] -8% to 25% by weight, preferably 9% to 20% by weight, more preferably 10% to 15% by weight of particle size D 50 (DIN EN 725-5, ISO 13320) 1μm to 10μm, preferably D 50 The thickness is 2μm to 8μm, more preferably D. 50 2μm to

[0015] 5μm silicon carbide particles,

[0016] -10% to 30% by weight, preferably 12% to 20% by weight, more preferably 13% to 18% by weight of carbon black.

[0017] -The total of all components always equals 100% by weight;

[0018] - Press the connecting surfaces of at least two SiC preforms together;

[0019] - Dry at least two SiC preforms; and

[0020] - Heating at least two SiC preforms allows Si to permeate into the SiC preforms containing dried bonding paste, thereby obtaining a substantially bonded silicon-silicon carbide (SiSiC) ceramic assembly.

[0021] This method allows for the bonding of at least two SiC preforms to provide SiSiC ceramic components. A bonding slurry or paste is applied to the parts to be bonded. It is characterized by appropriate working time and consistency. As will be described in more detail below, the bonding slurry comprises the following components: SiC particles having a bimodal or trimodal particle distribution, carbon black, another carbon source as a binder, and a solvent (if desired) for adjusting the viscosity of the bonding slurry. To reduce pore formation, a centrifugal mixer is used to mix the slurry components. The bonding slurry promotes material-to-material bonding between the two ceramic preforms.

[0022] A bonding paste is placed on the bonding surface of at least one of at least two SiC preforms to be bonded into a larger component. The component must then be dried. Drying is complete when the paste surface no longer shows any tendency to adhere. The composite is then infiltrated with Si, which produces a substantial bond.

[0023] The SiC preform connected according to this method is a porous body containing silicon, carbon and / or silicon carbide.

[0024] In one embodiment of this method, at least one of the SiC preforms having at least one bonding surface is obtained by 3D printing. Therefore, this method also allows for the bonding of a 3D-printed SiC preform to another 3D-printed SiC preform or a SiC preform obtained by conventional non-printing methods. In this case, a bonding slurry or paste is applied to the parts to be bonded. The bonding slurry is applied, for example, to the contour of the SiC preform using a trowel, and to the flat surface of the SiC preform, for example, using screen printing or other methods. Due to the complexity of 3D-printed composites, they can be embedded in filler before they are subjected to pressure to avoid breakage (if subjected to axial forces).

[0025] The method according to the present invention has several advantages:

[0026] - The possibility of producing components from different SiC preforms to achieve desired local technical characteristics; reduced milling time and material savings;

[0027] Complex (support) structures can be drawn using 3D printing. Conventional SiC preforms can be used when modifications are required by technical specifications. This means that, for example, functional surfaces and complete support structures do not necessarily need to be milled from large blocks;

[0028] - Producing SiC preforms that exceed the printer's print volume or cannot be produced by 3D printing due to structural reasons;

[0029] Higher utilization of print volume is possible because components can be printed in smaller parts and then assembled. This allows for a higher packing density of components in the job box.

[0030] As described, compared to conventionally obtained SiC preforms, SiSiC ceramic composites obtained using 3D-printed preforms can have coarser SiC grain sizes. Therefore, the density of the 3D-printed SiC ceramic preform in its uninfiltrated state is 1.3 g / cm³. 3 Up to 3.0 g / cm 3 Preferred concentration: 1.5g / cm 3 Up to 2.5g / cm 3 More preferably 1.7 g / cm 3 Up to 2.2 g / cm 3 Density is measured by Archimedes' method and / or by geometry.

[0031] 3D printing methods for obtaining SiC preforms are described, for example, in WO 2018 / 206250 A1. The 3D printing methods described therein are based on molded bodies from composite materials (e.g., SiC), which are progressively built up from multiple layers by powder bed printing or binder jetting, wherein the layer thickness is from 50 μm to 250 μm.

[0032] When producing SiC preforms by 3D printing, various starting compositions are possible, preferably 80% to 98% by weight of SiC and 2% to 20% by weight of C. The average grain size of the primary SiC grains in the SiC preform used is 25 μm to 60 μm, preferably 40 μm to 55 μm.

[0033] To secure the underlying layer required for the molded body, a liquid fixing component consisting of an adhesive or a mixture of adhesive and hardener is used. This can be applied, for example, via a printhead. The fixing component should preferably well wet the powder, ensuring uniform distribution of the organic material. Consolidation of the printed areas within the layer can be achieved by removing the volatile portions of the fixing component or by heat- and / or light-induced crosslinking (e.g., using an IR or UV lamp). After consolidation, another layer of ceramic powder is applied. The fixing component is applied and consolidated according to the next layer of the desired molded body. This process is repeated until the molded body is established according to the layer model. The obtained SiC preform is infiltrated with silicon (Si).

[0034] The binder used in 3D printing can be cross-linked by heat and / or light, for example, by irradiating large areas or spots with IR or UV lamps. UV-curable components can be free radical or cationic UV curing systems or a mixture of both, such as acrylates, epoxy resins, enol ethers, and vinyl groups. Thermosetting binders can be components dried by a heat source and / or reaction. Exemplary components are phenolic resins, furan resins, epoxy resins, graphite resins, starch, sugar, or cellulose solutions. Binders can also be inorganic-based, such as water glass. A preferred binder is a phenolic resin.

[0035] The SiC preforms manufactured by 3D printing have a grain size of 25 μm to 60 μm, preferably 40 μm to 55 μm, and a four-point flexural strength of up to 250 MPa. The 3D-printed SiC preforms preferably have a structure in which the structure of each layer in the microstructure is no longer visually identifiable at the vertical cut edges of the component, for example, by optical microscopy or scanning electron microscopy.

[0036] As mentioned, embedding the 3D-printed SiC preform within a filler material is advantageous in order to avoid and protect it from breakage under pressure. Suitable filler materials can be polymer particles, sand, or SiO2 powder.

[0037] In a preferred embodiment, the bonding slurry used in this method comprises:

[0038] -50% to 70% by weight of adhesives,

[0039] -5% to 18% by weight of particle size D 50 (DIN EN 725-5, ISO 13320) 10μm to 20μm, preferably D 50 The thickness is 11 μm to 18 μm, more preferably D. 50 Silicon carbide particles ranging from 11 μm to 16 μm

[0040] -9% to 20% by weight of particle size D 50 (DIN EN 725-5, ISO 13320) 1μm to 10μm, preferably D 50 The thickness is 2μm to 8μm, more preferably D. 50 Silicon carbide particles ranging from 2μm to 5μm in size.

[0041] -12% to 20% carbon black,

[0042] -In a preferred embodiment, the total of all components always equals 100% by weight.

[0043] In a more preferred embodiment, the bonding slurry used in this method comprises:

[0044] -50% to 70% by weight of adhesives,

[0045] -8% to 15% by weight of particle size D 50 (DIN EN 725-5, ISO 13320) 10μm to 20μm, preferably D 50 The thickness is 11 μm to 18 μm, more preferably D. 50 Silicon carbide particles ranging from 11 μm to 16 μm

[0046] -10% to 15% by weight of particle size D 50 (DIN EN 725-5, ISO 13320) 1μm to 10μm, preferably D 50 The thickness is 2μm to 8μm, more preferably D. 50 Silicon carbide particles ranging from 2μm to 5μm in size.

[0047] -13% to 18% carbon black,

[0048] -In a preferred embodiment, the total of all components always equals 100% by weight.

[0049] In another preferred embodiment, the bonding slurry comprises:

[0050] -40% to 80% by weight, preferably 50% to 70% by weight, of adhesive.

[0051] -2% to 20% by weight, preferably 5% to 18% by weight, more preferably 8% to 15% by weight of particle size D 50 The thickness is 30μm to 65μm, preferably D. 50 The thickness is 35 μm to 60 μm, more preferably D. 50 Silicon carbide particles ranging from 40μm to 55μm in size.

[0052] -2% to 20% by weight, preferably 5% to 18% by weight, more preferably 8% to 15% by weight of particle size D 50 The thickness is 10 μm to 20 μm, preferably D. 50 The thickness is 11 μm to 18 μm, more preferably D. 50 Silicon carbide particles ranging from 11 μm to 16 μm, and / or

[0053] -8% to 25% by weight, preferably 9% to 20% by weight, more preferably 10% to 15% by weight of particle size D 50 The thickness is 1μm to 10μm, preferably D. 50 The thickness is 2μm to 8μm, more preferably D. 50 Silicon carbide particles ranging from 2μm to 5μm in size.

[0054] -10% to 30% by weight, preferably 12% to 20% by weight, more preferably 13% to 18% by weight of carbon black.

[0055] -In a preferred embodiment, the total of all components always equals 100% by weight.

[0056] In another embodiment, the bonding slurry comprises:

[0057] -40% to 80% by weight, preferably 50% to 70% by weight, of adhesive.

[0058] -1% to 20% by weight, preferably 4% to 15% by weight, more preferably 6% to 10% by weight of particle size D 50 The thickness is 30μm to 65μm, preferably D. 50 The thickness is 35 μm to 60 μm, more preferably D. 50 Silicon carbide particles ranging from 40 μm to 55 μm, and

[0059] -1% to 20% by weight, preferably 4% to 15% by weight, more preferably 6% to 10% by weight of particle size D50 The thickness is 10 μm to 20 μm, preferably D. 50 The thickness is 11 μm to 18 μm, more preferably D. 50 Silicon carbide particles ranging from 11 μm to 16 μm

[0060] -8% to 25% by weight, preferably 9% to 20% by weight, more preferably 10% to 15% by weight of particle size D 50 The thickness is 1μm to 10μm, preferably D. 50 The thickness is 2μm to 8μm, more preferably D. 50 Silicon carbide particles ranging from 2μm to 5μm in size.

[0061] -10% to 30% by weight, preferably 12% to 20% by weight, more preferably 13% to 18% by weight of carbon black.

[0062] -In a preferred embodiment, the total of all components always equals 100% by weight.

[0063] In another preferred embodiment, the bonding slurry comprises:

[0064] -40% to 80% by weight, preferably 50% to 70% by weight, of adhesive.

[0065] -2% to 20% by weight, preferably 5% to 18% by weight, more preferably 8% to 15% by weight of particle size D 50 The thickness is 30μm to 65μm, preferably D. 50 The thickness is 35 μm to 60 μm, more preferably D. 50 Silicon carbide particles ranging from 40μm to 55μm in size.

[0066] -8% to 25% by weight, preferably 9% to 20% by weight, more preferably 10% to 15% by weight of particle size D 50 The thickness is 1μm to 10μm, preferably D. 50 The thickness is 2μm to 8μm, more preferably D. 50 Silicon carbide particles ranging from 2μm to 5μm in size.

[0067] -10% to 30% by weight, preferably 12% to 20% by weight, more preferably 13% to 18% by weight of carbon black.

[0068] -In a preferred embodiment, the total of all components always equals 100% by weight.

[0069] In a more preferred embodiment, the bonding slurry comprises:

[0070] -50% to 70% by weight of adhesives,

[0071] -5% to 18% by weight of particle size D 50 The thickness is 30μm to 65μm, preferably D. 50 The thickness is 35 μm to 60 μm, more preferably D. 50 Silicon carbide particles ranging from 40μm to 55μm in size.

[0072] -5% to 18% by weight of particle size D 50 The thickness is 10 μm to 20 μm, preferably D. 50 The thickness is 11 μm to 18 μm, more preferably D. 50 Silicon carbide particles ranging from 11 μm to 16 μm, and / or

[0073] -9% to 20% by weight of particle size D 50 The thickness is 1μm to 10μm, preferably D. 50 The thickness is 2μm to 8μm, more preferably D. 50 Silicon carbide particles ranging from 2μm to 5μm in size.

[0074] -12% to 20% carbon black,

[0075] -In a preferred embodiment, the total of all components always equals 100% by weight.

[0076] In another embodiment, the bonding slurry comprises:

[0077] -50% to 70% by weight of adhesives,

[0078] -4% to 15% by weight of particle size D 50 The thickness is 30μm to 65μm, preferably D. 50 The thickness is 35 μm to 60 μm, more preferably D. 50 Silicon carbide particles ranging from 40 μm to 55 μm, and

[0079] -4% to 15% by weight of particle size D 50 The thickness is 10 μm to 20 μm, preferably D. 50 The thickness is 11 μm to 18 μm, more preferably D. 50 Silicon carbide particles ranging from 11 μm to 16 μm

[0080] -9% to 20% by weight of particle size D 50 The thickness is 1μm to 10μm, preferably D. 50 The thickness is 2μm to 8μm, more preferably D. 50 Silicon carbide particles ranging from 2μm to 5μm in size.

[0081] -12% to 20% carbon black,

[0082] -In a preferred embodiment, the total of all components always equals 100% by weight.

[0083] In yet another preferred embodiment, the bonding slurry comprises:

[0084] -50% to 70% by weight of adhesives,

[0085] -5% to 18% by weight of particle size D 50 The thickness is 30μm to 65μm, preferably D. 50 The thickness is 35 μm to 60 μm, more preferably D. 50 Silicon carbide particles ranging from 40μm to 55μm in size.

[0086] -9% to 20% by weight of particle size D 50 The thickness is 1μm to 10μm, preferably D. 50 The thickness is 2μm to 8μm, more preferably D. 50 Silicon carbide particles ranging from 2μm to 5μm in size.

[0087] -12% to 20% carbon black,

[0088] -In a preferred embodiment, the total of all components always equals 100% by weight.

[0089] In one preferred embodiment, the bonding slurry comprises:

[0090] -50% to 70% by weight of adhesives,

[0091] -8% to 15% by weight of particle size D 50 The thickness is 30μm to 65μm, preferably D. 50 The thickness is 35 μm to 60 μm, more preferably D. 50 Silicon carbide particles ranging from 40μm to 55μm in size.

[0092] -8% to 15% by weight of particle size D 50 The thickness is 10 μm to 20 μm, preferably D. 50 The thickness is 11 μm to 18 μm, more preferably D. 50 Silicon carbide particles ranging from 11 μm to 16 μm, and / or

[0093] -10% to 15% by weight of particle size D 50 The thickness is 1μm to 10μm, preferably D. 50 The thickness is 2μm to 8μm, more preferably D. 50 Silicon carbide particles ranging from 2μm to 5μm in size.

[0094] -13% to 18% carbon black,

[0095] -In a preferred embodiment, the total of all components always equals 100% by weight.

[0096] In a preferred embodiment, the bonding slurry comprises:

[0097] -50% to 70% by weight of adhesives,

[0098] -8% to 15% by weight of particle size D 50 The thickness is 30μm to 65μm, preferably D. 50 The thickness is 35 μm to 60 μm, more preferably D. 50 Silicon carbide particles ranging from 40μm to 55μm in size.

[0099] -8% to 15% by weight of particle size D 50 The thickness is 10 μm to 20 μm, preferably D. 50 The thickness is 11 μm to 18 μm, more preferably D. 50 Silicon carbide particles ranging from 11 μm to 16 μm, and / or

[0100] -10% to 15% by weight of particle size D 50 The thickness is 1μm to 10μm, preferably D. 50 The thickness is 2μm to 8μm, more preferably D. 50 Silicon carbide particles ranging from 2μm to 5μm in size.

[0101] -13% to 18% carbon black,

[0102] -In a preferred embodiment, the total of all components always equals 100% by weight.

[0103] In another preferred embodiment, the bonding slurry comprises:

[0104] -50% to 70% by weight of adhesives,

[0105] -8% to 15% by weight of particle size D 50 The thickness is 30μm to 65μm, preferably D. 50 The thickness is 35 μm to 60 μm, more preferably D. 50 Silicon carbide particles ranging from 40μm to 55μm in size.

[0106] -10% to 15% by weight of particle size D 50 The thickness is 1μm to 10μm, preferably D. 50 The thickness is 2μm to 8μm, more preferably D. 50 Silicon carbide particles ranging from 2μm to 5μm in size.

[0107] -13% to 18% carbon black,

[0108] -In a preferred embodiment, the total of all components always equals 100% by weight.

[0109] It should be noted that the particle size of the silicon carbide particles is suitable for the ceramic material of the ceramic preform to be bonded, and the silicon carbide particles can be provided in a bimodal or trimodal distribution, but are preferably provided in a bimodal size distribution. This has the advantage that the bonding paste mimics the material of the SiC preform to be bonded, that is, the material properties of the bonding paste are similar to the material properties of the surrounding SiC preform.

[0110] The binder used in the bonding slurry is preferably an organic material that has been coked or pyrolyzed at or below the permeation temperature of the ceramic material; that is, the organic material is converted into carbon during the coking process. The binder is particularly derived from renewable organic sources such as starch or sugar, thus providing an eco-friendly alternative to commonly used phenolic resins or polymers. The binder can be added as a solution or suspension, preferably as an aqueous solution or aqueous suspension.

[0111] In one embodiment, the bonding slurry may further contain or include a solvent, preferably water, or a mixture of at least two solvents, for adjusting the viscosity of the slurry. In most cases, water is added to the slurry, preferably as a solution or suspension along with the binder. The amount of solvent, particularly water, in the bonding slurry can be up to 20% by weight, for example, from 2% to 20% by weight.

[0112] Use the following mixing parameters to mix the components of the bonding slurry: 400 rpm for 80 seconds, 600 rpm for 100 seconds, and 800 rpm for 120 seconds. Repeat this procedure 6 to 8 times. The mixing process should be carried out at atmospheric pressure or in a vacuum.

[0113] It should be understood that the bonding paste can be heated to a temperature up to 150°C, for example, RT to 150°C, preferably 40°C to 100°C, and more preferably 50°C to 90°C. Heating or tempering the bonding paste reduces its viscosity and facilitates its application to the surface of the ceramic component. Drying is carried out for at least 6 hours, preferably more than 6 hours.

[0114] The area of ​​the bonding surface of at least two SiC preforms may contain cavities, which should remain cavities after infiltration bonding. Therefore, at least one of the at least two SiC preforms may provide cavities in the area of ​​the bonding surface. These cavities may be filled with a filler material prior to infiltration to prevent Si from entering the cavities. This filler material does not react with the liquid Si-based metal during the infiltration of the at least two SiC preforms containing the bonding slurry. The filler material may be, for example, a boron nitride-based paste and can be removed from the cavities after the infiltration step, preferably without residue. The use of a filler material is important for the internal cavities because, due to capillary forces and the cooling behavior of Si, the cavities may be additionally filled with Si during infiltration.

[0115] The bonding paste is applied to one or both of the bonding surfaces of the two ceramic preforms to be bonded by means of a doctor blade, screen printing, spraying, or any other suitable method. The bonding paste is applied only to the areas of the bonding surface that should be bonded after Si infiltration. No bonding paste is applied to surfaces with or without filler material.

[0116] The bonding slurry is placed on the bonding surface in an amount that results in a slurry layer thickness of up to 200 μm, for example, 10 μm to 200 μm, preferably 30 μm to 150 μm, and more preferably 50 μm to 100 μm.

[0117] After the bonding slurry is applied to the surfaces to be bonded, the bonding surfaces of at least two composites are placed on top of each other, such that the bonding surfaces are in contact with each other. The bonding surfaces of at least two SiC preforms can be pressed together for at least 3 hours, preferably more than 5 hours. In one embodiment, the bonding surfaces of at least two SiC preforms are compressed or pressed together under a pressure of at least 0.3 MPa (3 bar), preferably at least 0.5 MPa (5 bar), for at least 3 hours, preferably at least 5 hours.

[0118] In subsequent steps, at least two ceramic SiC preforms and the bonding slurry are dried at a temperature of 20°C (preferably room temperature) to 150°C, preferably 40°C to 100°C, and more preferably 50°C to 90°C. Drying is complete when the surface of the bonding slurry does not show any tendency to adhere.

[0119] The drying loss of the binder slurry (determined according to DIN 51078, DIN EN 51078) is 5% to 70% by weight, preferably 6% to 60% by weight, more preferably 8% to 50% by weight (drying parameters: drying temperature 105°C, shut-off criterion: weight loss less than 1 mg within 120 seconds). The loss on ignition in oxygen at 1000°C, as determined according to DIN 51081, ISO 806, is 40% to 80% by weight, preferably 50% to 75% by weight, more preferably 60% to 75% by weight.

[0120] By using the bonding paste as described, SiSiC is formed in the bonding seam instead of a pure Si layer. Therefore, the bonding seam connecting at least two SiC preforms is preferably chemically nearly identical to the surrounding material of the resulting SiSiC assembly's body material. However, varying amounts of silicon may be present.

[0121] The joint may contain up to 50% by volume, preferably up to 30% by volume, for example 8% to 30% by volume of silicon, while the amount of silicon in the ceramic composite surrounding the joint is no more than 25% by volume, preferably 10% to 20% by volume.

[0122] In one embodiment, the material of the joint comprises at least 50 vol% silicon carbide and at least 8 vol% silicon, advantageously 50 vol% to 92 vol% silicon carbide and 8 vol% to 50 vol% silicon, and even more advantageously 70 vol% to 92 vol% silicon carbide and 8 vol% to 30 vol% silicon, wherein the sum of all phases always totals 100 vol%.

[0123] The silicon content in the seam was determined through image analysis. Therefore, the area of ​​the seam to be analyzed was marked in the first step. Subsequently, the silicon was marked using a range of grayscale values. Software (Stream from Olympus) determined the portion or percentage of pixels in the marked area corresponding to the silicon content in the analysis area.

[0124] The thickness of the joint is similar to the thickness of the joint grout layer and is up to 200 μm, preferably up to 100 μm, for example 10 μm to 200 μm, preferably 30 μm to 150 μm, and more preferably 50 μm to 100 μm.

[0125] This bonding and drying process provides a porous SiC assembly that can be permeated with liquid Si to fill the pores of the ceramic material and form a SiSiC assembly (see [link]). Figure 1 ).

[0126] Therefore, this method allows for the provision of SiSiC ceramic components:

[0127] -At least two SiC preforms are physically bonded together.

[0128] -At least two SiC preforms are infiltrated with a dried bonding slurry containing Si.

[0129] In a preferred embodiment, this method allows for the provision of SiSiC ceramic components:

[0130] -At least two SiC preforms are physically bonded together.

[0131] -At least one of the SiC preforms is a porous SiC ceramic preform obtained by 3D printing, and

[0132] - In this process, porous SiC preforms are infiltrated with a Si-containing bonding slurry to bond at least two SiC preforms together.

[0133] Using this bonding slurry, SiSiC is formed in the bonding seam instead of a Si layer, thus creating a material-to-material bond. In the case of SiSiC materials, the SiC particles present before Si infiltration are called primary SiC, and the SiC grains formed during infiltration by the reaction of carbon located in the preform or bonding slurry with the infiltrated liquid Si are called secondary SiC. The bonding seam of the SiSiC assembly contains primary SiC from the bonding slurry. Furthermore, secondary SiC is formed from the carbon source of the bonding slurry and the liquid Si from the infiltration step, resulting in a bonding seam having the same phase as the SiSiC surrounding it. The bonded material exhibits advantageous characteristics comparable to the bulk material.

[0134] The ceramic component obtained by the above method achieves at least 65%, preferably at least 75%, more preferably at least 80%, and most preferably at least 85% of the mechanical strength of the monolithic ceramic material (i.e., ceramic material without joints). The flexural strength is determined using a bending specimen made of two specimens longitudinally connected in the middle, according to the four-point measurement method of DIN 843-1, 843-5, ISO 14704, and ASTM C1161-13.

[0135] In contrast, in join assemblies containing only Si in the joint, less than 50% of the mechanical strength can be achieved. If adhesive is used for joining, the carbon in the adhesive may react to form secondary SiC at the interface between the SiC preform and the joint. The joint remains primarily composed of Si because the secondary SiC formed from the carbon derived from the adhesive decreases with distance from the interface with the SiC preform to the midpoint of the joint. Therefore, when adhesive is used to join at least two SiC preforms, less than 60% of the mechanical strength of the bulk material can be achieved.

[0136] The ceramic components obtained by this method can be used in wafer processing systems (i.e., wafer stages), sensors, cooling systems, heat exchangers, collectors, and sensor frames.

[0137] The invention will now be described in more detail with reference to embodiments and accompanying drawings. The drawings illustrate...

[0138] Figure 1 The final ceramic component obtained according to a first embodiment of the invention;

[0139] Figure 2 A ceramic assembly obtained by joining two ceramic SiC preforms without a connecting slurry;

[0140] Figure 3 Microscopic view of the seam in the final SiSiC ceramic assembly according to the present invention;

[0141] Figure 4 A connecting seam in a component according to a second embodiment of the present invention;

[0142] Figure 4 B Figure 4 Enlargement of the seam of A;

[0143] Figure 5 Non-Si-permeable bonded SiSiC ceramic components obtained by connecting 3D-printed SiC ceramic composites and (standard) SiC preforms.

[0144] Example 1:

[0145] To bond two SiC preforms, a bonding paste is used, which contains SiC particles, carbon black, and other carbon sources such as polymers. Here is an example of a bonding paste composition: starch solution: 55 wt%, FEPA abrasive particle size F500 SiC powder: 14 wt%, FEPA abrasive particle size F1200 SiC powder: 10 wt%, carbon black / graphite: 14 wt%. This bonding paste is applied via screen printing or other processes.

[0146] Example 2:

[0147] Here is another example of the composition of the bonding paste: starch solution: 62 wt%, SiC powder with FEPA abrasive size F500: 10 wt%, SiC powder with FEPA abrasive size F1200: 10 wt%, carbon black / graphite: 10 wt%, water 8 wt%. The bonding paste is applied to the bonding surface area of ​​at least one of the SiC preforms by screen printing or other processes.

[0148] Example 3:

[0149] Here is another example of the composition of the bonding paste: starch solution: 50 wt%, FEPA abrasive SiC powder: 12 wt%, FEPA abrasive F1200 SiC powder: 16 wt%, carbon black / graphite: 17 wt%, water: 5 wt%. The bonding paste is applied to the bonding surface area of ​​at least one of the SiC preforms by screen printing or other processes.

[0150] The two SiC preforms were then pressed together at a pressure greater than 5 bar for >5 hours and subsequently dried at 50°C to 90°C for >6 hours. This bonding and drying process provides porous SiC modules that can be permeated with liquid Si to fill the pores of the ceramic material and form SiSiC modules.

[0151] By using a bonding slurry, a SiSiC layer is formed in the bonding joint instead of a pure Si layer during the infiltration step, resulting in substantial bonding.

[0152] In contrast, when joining two ceramic SiC preforms without a bonding slurry, the seam can be completely filled with Si, without providing a substantial bond, as in... Figure 2 This is the best view you can get from it.

[0153] Figure 3 The micrographs show the seam after Si infiltration bonding of two SiC preforms using the method of the present invention. The brighter areas reflect the regions of organosilicon (Si) within the seam. It is evident that the regions with more organosilicon are mostly aligned along the seam and partially interrupted by darker regions with almost no organosilicon. Figure 3 In the samples shown, the seam contains 8 vol% to 30 vol% organosilicon, while the amount of silicon in the ceramic composite surrounding the seam is only 2 vol% to 20 vol%.

[0154] Example 4:

[0155] To join two SiC preforms, a bonding slurry is used, which contains SiC particles, carbon black, and other carbon sources such as polymers.

[0156] The following is an example of the composition of the bonding paste: starch solution: 55 wt%, SiC powder with FEPA abrasive size F240 and / or F500: 14 wt%, SiC powder with FEPA abrasive size F1200: 10 wt%, carbon black / graphite: 14 wt%, water: 7 wt%. This bonding paste is applied to the bonding surface area of ​​at least one of the SiC preforms by screen printing or other processes.

[0157] Example 5:

[0158] Here is another example of the composition of the bonding paste: starch solution: 62 wt%, SiC powder with FEPA abrasive size F240 and / or F500: 10 wt%, SiC powder with FEPA abrasive size F1200: 10 wt%, carbon black / graphite: 10 wt%, water: 8 wt%. The bonding paste is applied to the bonding surface area of ​​at least one of the SiC preforms by screen printing or other processes.

[0159] Example 6:

[0160] Here is another example of the composition of the bonding paste: starch solution: 50 wt%, SiC powder with FEPA abrasive size F240 and / or F500: 12 wt%, SiC powder with FEPA abrasive size F1200: 16 wt%, carbon black / graphite: 17 wt%, water: 5 wt%. The bonding paste is applied to the bonding surface area of ​​at least one of the SiC preforms by screen printing or other processes.

[0161] The two SiC preforms were then pressed together at a pressure greater than 5 bar for >5 hours and subsequently dried at 50°C to 90°C for >6 hours. This bonding and drying process provides porous SiC modules that can be permeated with liquid Si to fill the pores of the ceramic material and form SiSiC modules.

[0162] Figure 4 A and 4B show the seams in components made from 3D porous SiC preforms (upper image area) and conventionally manufactured porous SiC preforms (lower image area) using the bonding slurry of any of Examples 4 to 6.

[0163] Figure 5 A SiSiC ceramic assembly is shown obtained by connecting a 3D-printed SiC ceramic composite (1) and a (standard) SiC preform (2).

[0164] This combination of 3D-printed SiC ceramic composites and standard SiC preforms is used when the complexity and geometry are difficult to produce economically using other manufacturing processes, and / or when only a small number of components are needed, such as for prototyping. In those cases, 3D printing is cheaper than new molds.

[0165] On the other hand, for larger quantities, conventional manufacturing has the advantages of better material properties and lower manufacturing costs.

[0166] Therefore, when a high level of complexity is required, the properties of the 3D-printed composite are too low, or the overall size of the component is larger than the volume of the 3D printer, a combination of 3D-printed SiC ceramic composites and standard SiC preforms is used.

Claims

1. A method for obtaining at least one ceramic component by joining at least two SiC preforms: - Provide at least two porous SiC preforms, each having at least one connecting surface, such as green parts or coking parts; - Provide a bonding slurry, the bonding slurry comprising -40% to 80% by weight, preferably 50% to 70% by weight, of at least one adhesive. -2% to 20% by weight, preferably 5% to 18% by weight, more preferably 8% to 15% by weight of particle size D 50 (DIN EN 725-5, ISO 13320) 10μm to 20μm, preferably D 50 The thickness is 11 μm to 18 μm, more preferably D. 50 Silicon carbide particles ranging from 11 μm to 16 μm -8% to 25% by weight, preferably 9% to 20% by weight, more preferably 10% to 15% by weight of particle size D 50 (DIN EN 725-5, ISO 13320) 1μm to 10μm, preferably D 50 The thickness is 2μm to 8μm, more preferably D. 50 Silicon carbide particles ranging from 2μm to 5μm in size. -10% to 30% by weight, preferably 12% to 20% by weight, more preferably 13% to 18% by weight of carbon black. -The total of all components always equals 100% by weight; - Press the connecting surfaces of the at least two SiC preforms together; - Drying the at least two SiC preforms; and - The at least two SiC preforms are heated, thereby allowing Si to permeate into the SiC preforms containing dried bonding slurry, resulting in a substantially bonded silicon-silicon carbide (SiSiC) ceramic assembly.

2. The method according to claim 1, characterized in that... At least one of the SiC preforms is obtained by 3D printing, and each has at least one connecting surface.

3. The method according to claim 2, characterized in that... At least one of the SiC preforms obtained by 3D printing has a density of 1.3 g / cm³ before Si infiltration. 3 Up to 3.0 g / cm 3 Preferred concentration: 1.5g / cm 3 Up to 2.5g / cm 3 More preferably 1.7 g / cm 3 Up to 2.2 g / cm 3 .

4. The method according to any one of claims 2 to 3, characterized in that 3D printed SiC preforms are embedded in filler material.

5. The method according to any one of claims 1 to 3, characterized in that... The bonding slurry comprises: -50% to 70% by weight of the at least one adhesive, -5% to 18% by weight of particle size D 50 (DIN EN 725-5, ISO 13320) 10μm to 20μm, preferably D 50 The thickness is 11 μm to 18 μm, more preferably D. 50 Silicon carbide particles ranging from 11 μm to 16 μm -9% to 20% by weight of particle size D 50 (DIN EN 725-5, ISO 13320) 1μm to 10μm, preferably D 50 The thickness is 2μm to 8μm, more preferably D. 50 Silicon carbide particles ranging from 2μm to 5μm in size. -12% to 20% carbon black, -In a preferred embodiment, the total of all components always equals 100% by weight.

6. The method according to any one of the preceding claims, characterized in that... The bonding slurry comprises: -50% to 70% by weight of the at least one adhesive, -8% to 15% by weight of particle size D 50 (DIN EN 725-5, ISO 13320) 10μm to 20μm, preferably D 50 The thickness is 11 μm to 18 μm, more preferably D. 50 Silicon carbide particles ranging from 11 μm to 16 μm -10% to 15% by weight of particle size D 50 (DIN EN 725-5, ISO 13320) 1μm to 10μm, preferably D 50 The thickness is 2μm to 8μm, more preferably D. 50 Silicon carbide particles ranging from 2μm to 5μm in size. -13% to 18% carbon black, -In a preferred embodiment, the total of all components always equals 100% by weight.

7. The method according to any one of the preceding claims, characterized in that... The bonding slurry comprises: -40% to 80% by weight, preferably 50% to 70% by weight of the at least one adhesive. -2% to 20% by weight, preferably 5% to 18% by weight, more preferably 8% to 15% by weight of particle size D 50 (DIN EN 725-5, ISO 13320) 30μm to 65μm, preferably D 50 The thickness is 35 μm to 60 μm, more preferably D. 50 Silicon carbide particles ranging from 40 μm to 55 μm, and / or -2% to 20% by weight, preferably 5% to 18% by weight, more preferably 8% to 15% by weight of particle size D 50 (DIN EN 725-5, ISO 13320) 10μm to 20μm, preferably D 50 The thickness is 11 μm to 18 μm, more preferably D. 50 Silicon carbide particles ranging from 11 μm to 16 μm -8% to 25% by weight, preferably 9% to 20% by weight, more preferably 10% to 15% by weight of particle size D 50 (DIN EN 725-5, ISO 13320) 1μm to 10μm, preferably D 50 The thickness is 2μm to 8μm, more preferably D. 50 Silicon carbide particles ranging from 2μm to 5μm in size. -10% to 30% by weight, preferably 12% to 20% by weight, more preferably 13% to 18% by weight of carbon black. -The total of all components always equals 100% by weight.

8. The method according to any one of the preceding claims, characterized in that... The at least one adhesive in the bonding slurry is an organic material, particularly derived from a recyclable organic source.

9. The method according to claim 9, characterized in that... The at least one adhesive in the bonding slurry comprises starch or sugar.

10. The method according to any one of the preceding claims, characterized in that... The bonding slurry contains at least one solvent, preferably water, or a mixture of at least two solvents, for adjusting the viscosity of the slurry.

11. The method according to claim 11, characterized in that... The solvent in the bonding slurry preferably consists of water in an amount of up to 20% by weight, particularly 2% to 20% by weight.

12. The method according to any one of the preceding claims, characterized in that... The thickness of the slurry layer is up to 200 μm, preferably up to 100 μm, for example 10 μm to 200 μm, preferably 30 μm to 150 μm, and more preferably 50 μm to 100 μm.

13. The method according to any one of the preceding claims, characterized in that... The connecting surfaces of the at least two SiC preforms are pressed together with the connecting slurry for at least 5 hours, preferably more than 5 hours.

14. The method according to any one of the preceding claims, characterized in that... The drying of the pressed SiC preforms is carried out at a temperature of 20°C to 150°C, preferably 40°C to 100°C, and more preferably 50°C to 90°C.

Citation Information

Patent Citations

  • Process for producing a ceramic component assembled from a plurality of preforms

    DE102011007815B4

  • Additive manufacturing of metal matrix composite materials

    WO2018206250A1

  • Ceramic component

    WO2019063833A1